Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1371/journal.pone.0171862
|View full text |Cite
|
Sign up to set email alerts
|

Lack of desensitization of the cough reflex in ovalbumin-sensitized rabbits during exercise

Abstract: IntroductionCough is a major symptom of asthma frequently experienced during exercise but little is known about interactions between cough and exercise. The goal of our study was to clarify the potential modulation of the cough reflex (CR) by exercise in a spontaneously breathing anaesthetized animal model of airway eosinophilic inflammation.Materials & methodsTen ovalbumin (OVA) sensitized adult rabbits and 8 controls were studied. The ventilatory response to direct tracheal stimulation, performed both at res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 54 publications
0
13
1
Order By: Relevance
“…Central and peripheral mechanisms involved in exercise and voluntary isocapnic hyperventilation may downregulate the cough response (Lavorini et al, 2010;Poussel et al, 2014). However, exercise (electrically induced hindlimb muscular contractions) in ovalbumin-sensitized rabbits fails to produce similar effects (Tiotiu et al, 2017). An important characteristic of the cough reflex is its very strong dependency on the sleep-wakefulness state as well as on anesthesia (Nishino et al, 1988;Widdicombe and Singh 2006).…”
Section: Neuronal Recordings C-fos Immunohistochemistry and Lesion Ementioning
confidence: 99%
“…Central and peripheral mechanisms involved in exercise and voluntary isocapnic hyperventilation may downregulate the cough response (Lavorini et al, 2010;Poussel et al, 2014). However, exercise (electrically induced hindlimb muscular contractions) in ovalbumin-sensitized rabbits fails to produce similar effects (Tiotiu et al, 2017). An important characteristic of the cough reflex is its very strong dependency on the sleep-wakefulness state as well as on anesthesia (Nishino et al, 1988;Widdicombe and Singh 2006).…”
Section: Neuronal Recordings C-fos Immunohistochemistry and Lesion Ementioning
confidence: 99%
“…Exercise appears to modulate cough reflex response in a similar way as it does for the bronchomotor tone. Clinical studies in normal and asthmatic subjects and animal models of asthma have demonstrated airway dilation (Lee and Anderson, 1985 ; Cabral et al, 1999 ) and/or cough suppression (Lavorini et al, 2010 ; Tiotiu et al, 2017 ) during exercise while a transient airway narrowing (Lee and Anderson, 1985 ; Cabral et al, 1999 ; Anderson and Daviskas, 2000 ) and cough induction that occurs several minutes after exercise cessation is frequently seen in asthmatic subjects or athletes (Powell et al, 1996 ; Turmel et al, 2012 ; Bordeleau et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which the physiologic adaptation can be altered has not been widely studied, however the association with airway inflammation is highly suggested (Hazucha et al, 1996 ). A recent demonstration of lack of cough down-regulation during electrical limb muscle stimulation in a rabbit model of late-phase response to allergen inhalation (Tiotiu et al, 2017 ) suggested a role for eosinophilic inflammation. A few studies conducted among high-level athletes showed a higher prevalence of cough during prolonged exercise or when performed under specific environmental conditions (Turmel et al, 2012 ; Boulet et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…As previously described (Tiotiu et al, 2017), rabbits were sensitized the month before the acute experiment (performed on day 29 on the trial calendar) according to the following protocol:…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have proven that CR is decreased during exercise in healthy subjects (Lavorini et al, 2010;Demoulin-Alexikova et al, 2017) as well as in animal models (Poussel et al, 2014), even the precise underlying mechanisms are still debated. In contrast, CR sensitivity during exercise was unchanged (i.e., lack of downregulation) in ovalbumin (OVA)-sensitized rabbits (eosinophilic bronchial inflammation mimicking classical asthmatic inflammation) (Tiotiu et al, 2017), suggesting the contribution of bronchial eosinophilic inflammation in the modulation of CR in asthmatics during exercise.…”
Section: Introductionmentioning
confidence: 99%